Echocardiographic Assessment of Left Ventricular Remodeling in Hypertensive Patients: Systematic Review and Meta-Analysis - H, Alsrur, Hamad Hamoud; Zain, Zarihah binti Mohd (Journal of Ecohumanism, 2024)
Left ventricular remodeling is typically observed in coronary artery disease (CAD) and hypertensive heart disease (HHD). Consequently, it is of paramount significance to evaluate the left ventricular remodeling of CAD and HHD, as it may significantly impact the therapeutic choices, prognosis, and diagnosis.This meta-analysis assessed left ventricular remodeling in hypertensive cases using echocardiography.The systematic review and meta-analysis have been carried out in line with the PRISMA guidelines. The research involved published non-randomized investigations and randomized controlled trials (RCT) that assessed left ventricular remodeling in hypertensive patients using echocardiography. A thorough search has been carried out in electronic databases, including Scopus, PubMed, Cochrane Library, MEDLINE, and Web of Science, utilizing MeSH and text keywords such as “Hypertension,” “Hypertensive Patients,” “cardiac remodeling,” “Left Ventricular Remodeling,” “speckle tracking echocardiography,” and “3D echocardiography.”A total of 7 studies have been selected for the present analysis, including a total of 2174 cases. The combined outcome demonstrates highly statistically significant variance among groups according to SBP (Z = 3.29, P ˂0.001). The combined outcome demonstrates statistically significant variance among groups according to DBP (Z-value = 2.87, P-value =0.004). Result demonstrates statistically insignificant variance among groups according to HR (Z-value = 1.66, P-value =0.10). The combined outcome demonstrates statistically insignificant variance among groups according to aortic Dimensions (Z-value = 1.04, P-value =0.30). The combined outcome demonstrates highly statistically significant variance among groups according to Left atrial diameter (Z = 9.37, P˂0.001). The combined outcome demonstrates statistically significant variance among groups according to interventricular septum dimension (Z = 4.34, P <0.001). The combined outcome demonstrates statistically insignificant variance among groups according to posterior wall dimension (Z = 1.61, P =0.11). The combined outcome demonstrates highly statistically significant variance among groups according to left ventricle mass (Z-value = 3.93, P-value <0.001).This research concluded that in hypertensive cases with essentially preserved left ventricle systolic function, significant impairment of left ventricle diastolic and systolic functions was observed, particularly when correlated with LVH, as demonstrated by 2D and 3D speckle tracking echocardiography.